Spatial lipidomics reveals demyelination and remyelination dynamics in the mouse brain - Opielka, Mikolaj; Urbanowicz, Krzysztof; Konieczna-Wolska, Klaudia; Müller, Elisabeth; Krajewski, Oliwier; Feucherolles, Maureen; Zhou, Qiuqin; Bienkowski, Michal; Frache, Gilles; Hopf, Carsten; Schirmer, Lucas; Rutkowska, Aleksandra; et al. (Journal of lipid research, 2025)
Myelin pathology in demyelinating diseases is accompanied by lipid remodeling that remains challenging to characterize at the spatial level using traditional mass spectrometry. We developed an optimized AP-MALDI-Orbitrap MSI pipeline, incorporating sample preparation improvements and mass recalibration, to investigate lipid dynamics in the cuprizone (CPZ) mouse model of demyelination. Dual-modality, untargeted lipid profiling was performed to map spatially resolved lipid alterations during demyelination and spontaneous remyelination in two key brain areas of male mice: corpus callosum (CC) and cortex (Ctx), with lipid identifications benchmarked against 4D-LC-TIMS-MS/MS. Demyelinated regions were identified using Black Gold II staining. Using 1 ppm mass tolerance, we annotated 154 and 133 lipids at the sum-composition level in CC and Ctx, respectively, with 60% validated by LC-MS/MS. Spatial lipid profiling revealed CPZ-induced alterations in sphingolipids, sulfatides, and glycerophospholipids, supported by reanalysis of a published snRNA-seq dataset from a mouse CPZ model. Long-chain ceramides (Cer) and hexosylceramides (HexCer) were reduced in demyelinated regions, with partial, region-specific recovery during remyelination. Short-chain sulfatides (SHexCer), sphingomyelins (SM), and seminolipids transiently increased in the CC during demyelination, while long-chain sulfatides decreased in both CC and Ctx. Additionally, we observed demyelination-induced upregulation of polyunsaturated glycerophospholipids in CC and phosphatidylinositols (PI) in cortex. Lipid subclass changes emerged as reliable markers of both demyelination and remyelination in the mouse brain. Region-specific alterations in lipid metabolism provide new insights into the processes of de- and remyelination. Notably, remyelinated fibers have a distinct lipid profile compared to intact myelin, suggesting that lipid-based therapeutic strategies could improve myelin repair.
Online verfügbar: 23. September 2025, Artikelversion: 6. November 2025
Gesehen am 27.01.2026